Feasibility of an Integrated Digital and Pharmacological Approach Targeting Blood Lipids in Atherosclerotic Cardiovascular Disease Management - Xu Yi; Qiu Weiyu; Li Yan; Lan Xianwu; Wu Shaorong (Cardiovascular Innovations and Applications)
Objectives: Strong evidence supports the importance of lipid-lowering and exercise therapies in the long-term therapy of atherosclerotic cardiovascular disease (ASCVD). Establishing efficient comprehensive intervention programs that combine pharmacological and exercise prescription is crucial to investigate with the aid of digital technologies. Methods: A convenience sample of 25 ASCVD patients (57.8 ± 9.5 years, 76% males) was gathered. All participants were prescribed with 12-week home exercise program supervised by an app and bimonthly 75mg alirocumab subcutaneous injections. Follow up visits were scheduled at the end of 4th and 12th week. Results: Nineteen participants completed the program with a retention rate of 76%. Sixteen (84.2%) participants received all six doses of alirocumab. The total management time of the 12-week program added up to 65.47 minutes per patient. Satisfaction score was 4.2 ± 0.6 and the User Version of the Mobile Application Rating Scale (uMARS) overall objective quality score on the app was 3.4 ± 0.7. At the 4-week and 12-week follow-ups, LDL-C levels reduced compared to baseline (−1.5 ± 0.8 mmol/L, P < 0.001, −1.6 ± 0.8 mmol/L, P < 0.001, respectively), along with TC (−1.8 ± 1.2 mmol/L, P < 0.001, −1.6 ± 1.3 mmol/L, P < 0.001, respectively), but not TG, HDL-C, GAD-7 and PHQ-9. Conclusion: The integrated pharmaceutical and digital ERx intervention program was feasible and well accepted in ASCVD patients.